1994
DOI: 10.1289/ehp.94102s485
|View full text |Cite
|
Sign up to set email alerts
|

Chemical analysis and biological testing of a polar fraction of ambient air, diesel engine, and gasoline engine particulate extracts.

Abstract: SwedenExtracts of gasoline and diesel vehicle exhaust and ambient air particles were fractionated into five fractions according to polarity on a silica gel column. Two medium polar fractions showing high genotoxic activity in the Ames test were further subfractionated, using normal-phase high-performance liquid chromatography. Chemical analyses were performed by means of gas chromatography combined with mass spectrometry and flame ionization and detection. The crude extracts, fractions, and subfractions were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…They contain various substances that stimulate Ah receptors such as the polycyclic aromatic hydrocarbon containing benzo[a]pyrene. They also include gas and large quantities of carbonaceous particles, which absorb polyaromatic hydrocarbons and trace amounts of heavy metals (Strandell et al. , 1994).…”
Section: Introductionmentioning
confidence: 99%
“…They contain various substances that stimulate Ah receptors such as the polycyclic aromatic hydrocarbon containing benzo[a]pyrene. They also include gas and large quantities of carbonaceous particles, which absorb polyaromatic hydrocarbons and trace amounts of heavy metals (Strandell et al. , 1994).…”
Section: Introductionmentioning
confidence: 99%
“…This is the first report of human lung tissue‐catalyzed bioactivation of diesel exhaust constituents to genotoxicants. We did not determine the SRM 1975 constituents involved in the mutagenicity but PAHs and NPAHs were the most likely major contributors, based on the established role of the two classes of compounds in DEPE mutagenicity [Claxton, ; IARC, ; Stradell et al, ; Hughes et al, ; Seagrave et al, ; DeMarini, ], and on our observed effects of enzyme inhibitors on the mutagenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Other DEP constituents implicated in DEPE and DEP mutagenicity include oxygenated PAHs and heterocyclic arylamines [Manabe et al, 1993]. Additional directly mutagenic non‐NPAH constituents have also been reported but not well characterized [Crebelli et al, ; Stradell et al, ]. These agents are all relevant to the health effects of diesel exhaust emission samples, which vary in chemical composition, depending on several factors, including engine type, fuel formulation, duty cycle, and sampling methods [Claxton, ; Schuetze, ; Rosenkranz, ].…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of atmospheric OPAHs might be higher because PAHs in the atmosphere are more susceptible to photochemical transformation than PAHs in the soil [155]. Atmospheric sampling studies of OPAH have found concentrations in the approximate range 0.1-10 ng/m 3 for a number of OPAH [164,165].…”
Section: Exposure To Opahsmentioning
confidence: 99%
“…Some OPAHs are mutagenic in bacterial and human cell mutation assays [165,[177][178][179]. In addition, OPAHs are compounds enriched in the semipolar fractions of atmospheric particulate extracts; fractions that are highly mutagenic in bacterial and human cells [165]. In addition to the genotoxic effects of PAHs in the PM, particulate air pollution also induces oxidative damage to DNA [55].…”
Section: Biological Relevance Of Opahmentioning
confidence: 99%